Process Evaluation of Internet-Based Cognitive Behavioral Therapy Intervention for Informal Caregivers - Biliunaite, Ieva; Kazlauskas, Evaldas; Sanderman, Robbert; Andersson, Gerhard (Frontiers in Medicine, 2021)
Background: Informal caregivers are individuals who provide care for ill, frail, or otherwise dependent family members, siblings, or friends. Due to the caregiving demands, informal caregivers are known to experience negative mental health symptoms, such as stress or anxiety. Interventions based on Internet-based Cognitive Behavioral Therapy (ICBT) principles have been previously found to be effective for different populations and could also be considered as a plausible support option for informal caregivers. However, findings regarding effectiveness alone might not be sufficient for informing about the overall feasibility of the intervention. Objective: The aim of this process evaluation study was to evaluate the feasibility of a previously developed ICBT intervention for informal caregivers in Lithuania. More specifically, we evaluated the suitability of the intervention in relation to its content and delivery mode. Methods: Two studies were conducted. Study 1 consisted of participant evaluations of an 8-week, 8-module long therapist supported ICBT intervention. Evaluations for the Study 1 were retrieved from previously unused data, obtained from pilot testing of the intervention in which 63 informal caregivers took part. The evaluations contained of qualitative data (participant comments), as well as quantitative data (evaluations of each of the sessions). The Study 2 was an online stakeholder focus-group discussion conducted via Zoom. Eight stakeholders took part in the discussion, among whom there were social workers, medical professionals as well as individuals with caregiving experience themselves. Data were analyzed using descriptive statistics, thematic analysis, and data coding. Results: Results of the Study 1 showed that most of the pilot randomized controlled trial participants evaluated content and format of the intervention positively. These results were complemented by the findings in the Study 2, in which stakeholders evaluated the intervention as suitable and promising. In addition, stakeholders made certain suggestions for improving the intervention's usability for the informal caregivers. This included improving the instructions, providing with more guidance, and considering personalization options. Conclusion: The process evaluation helped to evaluate the feasibility of the ICBT intervention for informal caregivers in Lithuania from the two perspectives: users and stakeholders. Our findings suggest that the intervention is suitable for the target population.